Experiences of the informal caregiver of the disabled patient in the home setting - Lema Espinel, Jessica Paola (2022)
Introduction: Informal caregivers are a fundamental pillar since they are directly responsible for the daily care of the person with a disability. However, these lived experiences are very useful to learn about the role of caregivers. Objective: To analyze the experiences of informal caregivers of patients with disabilities at home. Methodology: the study had a qualitative approach with a phenomenological design, the population was a group of 10 people for which data saturation was considered. Interviews were used for subsequent data analysis and to represent the responses of the participants. Results and Discussion: with the interviews conducted, a categorization was elaborated which are: caregiver's beginnings, role of a caregiver, changes experienced when becoming a caregiver, caregiver's health and emotional state, and recommendations to other caregivers. In addition, improvement strategies were implemented for informal caregivers, for which it was executed in three stages such as: identifying the need, establishing plans and executing such plans Conclusion: through the results obtained and the triangulation of the same, it can be corroborated that the role of the informal caregiver in daily activities becomes experiences on nursing care, also fulfills the role as such as housework. In addition, positive and negative factors that are present in the daily experiences of caregivers were evidenced, and the implementation was fulfilled creating awareness in caregivers about their health care.